Peran Self Efficacy dan Iklim Organisasi dalam membentuk Employee Engagement melalui Komitmen Organisasi - Endy Pungkas Priambodo; Marcham Darokah; RR. Erita Yuliasesti Diah Sari (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This study aims to determine the effect of self-efficacy and organizational climate on employee engagement with organizational commitment as a mediator. The subjects who participated in this study were 110 employees of a travel agent company. Data was collected using scales namely Self-Efficacy, Organizational Climate, Organizational Commitment, and Employee Engagement scales and analyzed using SEM analysis techniques. The results  showed a significant effect of self-efficacy and organizational climate on employee engagement with organizational commitment as a mediator variable with a correlation coefficient r = 0.575 and r = 0,478 (significance level (p) = 0.001). These results indicate that organizational commitment can mediate self-efficacy towards Employee engagement by providing an effective contribution of 33.1% and mediating organizational climate of employee engagement with an effective contribution of 22.8.